PENGARUH BIAYA OPERASIONAL DAN BIAYA PROMOSI TERHADAP VOLUME PENJUALAN - Ade Elza Surachman (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
The purpose of this study is to analyze the effect of operational costs and operational costs on sales volume. The research method used is quantitative research. The data used is in the form of secondary data, namely the financial statements of PT. XYZ on type C motorcycle products in 2016-2020. Based on multiple linear regression analysis tests, the results of (1) operational costs did not have a significant effect on sales volume, (2) promotional costs did not have a significant effect on sales volume, and (3) operational costs and promotional costs did not have a significant effect on sales volume.